Knowledge based environment to support product design validation - Al-Ashaab, Ahmed; Molyneaux, M.; Doultsinou, Athanasia; Brunner, B.; Martínez, E.; Moliner, F.; Santamaría, V.; Tanjore, D.; Ewers, Paul; Knight, G. (Elsevier, 2012)
A knowledge-based environment to support product design validation of refresh projects (projects with minor changes in comparison with previous ones) has been developed. This was achieved by capturing the relation between the design change of refresh projects with their required physical tests and the historical data of previous projects. The refresh projects constitute the majority, around 60%, of the total number of projects in the collaborating company. The knowledge-based environment framework (Knowledge-Based Environment to Support Product Design Validation - KBE-ProVal) has been implemented on the Product Lifecycle Management Platform, called Teamcenter. The KBE-ProVal development was based on the standardisation of the existing related documents while maintaining the traceability of the decision making process. This implementation will avoid repeating unnecessary and costly physical product tests, thus reducing time and costs for these refresh projects